Perilaku Komunikasi Remaja Pengguna Aplikasi Tiktok (Studi Pada SMP 15 Bengkulu Selatan) - Desi Rahmadania; Anis Endang SM; Bayu Risdiyanto (Jurnal Multidisiplin Dehasen (MUDE), 2024)
This research aims to analyze the communication behavior of TikTok social media users, especially non-verbal communication behavior, especially among adolescents at SMPN 15 of South Bengkulu. This research uses a qualitative approach with data collection techniques in the form of interviews and observations of adolescents at SMPN 15 of South Bengkulu who use TikTok. This research uses communication theory according to Harold Dwight Lasswell. This theory suggests that a good way to explain the communication process is to answer five questions, namely: Who (who is the source), Says What (what is conveyed), In Which Channel (via what media), To Whom (who is the target), and With What Effect (what is the influence) 4. This theory can help identify the communication elements involved in using the TikTok application, as well as their impact on adolescent communication behavior. The results of the research show the Communication Behavior of TikTok Social Media Users at SMPN 15 of South Bengkulu, namely that they use TikTok social media because it is a trend nowadays. There are various interesting features on TikTok social media so that it can relieve the burden on your mind. Creating viral video content and sharing your own edits, educating TikTok social media users and channeling talents through TikTok social media, making TikTok social media a source of entertainment and information and what are the impacts of using TikTok social media, both positive and negative.